2018
DOI: 10.4103/ejd.ejd_187_17
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries prevalence and its association with fluoride level in drinking water in Sana’a, Yemen

Abstract: Objectives:Dental caries is the most prevalent chronic condition affecting schoolchildren worldwide. This study is aimed to assess the prevalence of dental caries among schoolchildren in urban and rural districts of Sana'a governorate, Yemen, and to investigate the correlation between caries experience and level of fluoride in drinking water, age, gender, and residence.Materials and Methods:This school-based survey involved 17,599 schoolchildren (aged 6–12 years), of whom 9623 were boys and 7976 were girls. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
1
11
1
1
Order By: Relevance
“…Besides, there was no meaningful relationship between DMFT and using sodium fluoride mouthwash by the students. Our findings are similar to the results of QUAN and colleagues (40) in China, but inconsistent with Al-Akwa et al study results (3). It seems quality of dental floss use and brushing plays an important role in the prevention of dental caries.…”
Section: Discussioncontrasting
confidence: 59%
“…Besides, there was no meaningful relationship between DMFT and using sodium fluoride mouthwash by the students. Our findings are similar to the results of QUAN and colleagues (40) in China, but inconsistent with Al-Akwa et al study results (3). It seems quality of dental floss use and brushing plays an important role in the prevention of dental caries.…”
Section: Discussioncontrasting
confidence: 59%
“…45,46 Therapeutic effect of fluoride on reducing the prevalence of dental caries has been widely reported. 47,48 Nevertheless, limitation of dosage according to the recommendations plays a key role to avoid further complications. 49 Although it is questionable to judge the validity of a publication based on citation counts, a strong association between impact on a field and high citation counts has been reported.…”
mentioning
confidence: 99%
“…Research by Al-Akwa et al [47] revealed a negative correlation between caries frequency and fluorine concentration in drinking water (0.61-2.00 ppm F -).…”
Section: Discussionmentioning
confidence: 98%